Behavioral Factors Influencing Investment Decisions among Nepalese Student Investors - Hamal, Janga Bahadur; Sharma, Dilli Raj; Manandhar, Ujen (Nepalese Journal of Business and Management Studies, 2024)
This study investigates the impact of heuristics and herding behavior on investment decision-making among 109 Nepalese student investors. While previous studies explored behavioral biases in developed markets, limited research focused on student investors in developing economies like Nepal. Based on prospect theory and dual process theory, it examines whether heuristics and herding affect students’ choices regarding buying, selling, and selecting stocks at the Nepal Stock Exchange. Using structured questionnaires, data was collected from a sample of 109 student investors enrolled in management courses at Tribhuvan University’s affiliated colleges in Kathmandu. Correlation analysis indicates positive relationships between investment decisions and both heuristics and herding. Regression analysis further demonstrates that heuristics and herding positively influence investment decisions. The findings contribute to behavioral finance understanding in developing economies and among student investors. They highlight the need for financial literacy and investor education initiatives to mitigate behavioral biases’ impact on decision-making. Integrating behavioral insights into curricula and policies can foster more rational investment choices among students.